Desenvolvimento de fotocatalisadores híbridos entre óxidos metálicos e complexo fac-[ClRe(CO)3(dcbH2)] com alta atividade para redução de CO2 em CO sob irradiação visível - Silva, Gabriela Nunes (2023)
The environmental problems associated with the consumption of energy from non-renewable sources have intensified the emission of carbon dioxide (CO2) into the atmosphere, which is the main greenhouse gas responsible for causing climate changes that can endanger life on earth. According to data from the Global Monitoring Laboratory, there has been an increase of more than 130 ppm in the global emission of CO2 since the industrial revolution. Thus, to simultaneously circumvent possible energy and environmental problems, photocatalysis emerges as a key technology for converting CO2 into higher value-added products using solar energy as renewable energy source. In this work, the photoreduction of CO2 was investigated through the synthesis of hybrid materials between semiconductor oxides: niobium pentoxide (Nb2O5), exfoliated hexaniobate (K4-xHxNb6O17esf) and copper oxide (CuO) with the molecular catalyst fac-[ClRe (CO)3(dcbH2)], dcbH2 =-4,4'-dicarboxylic acid-2,2'-bipyridine. The hybrid systems allow for the combination of advantages from the semiconductors, such as the high stability in the reaction medium, with the high selectivity of the molecular catalyst, allowing to maximize the electronic transfer between the components, so that the photocatalytic reduction of CO2 to CO can occur under visible light. The results obtained show that the composite formed by the heterostructure of niobium pentoxide treated at 180 ºC with 1% copper oxide sensitized with the Re(I) complex (Re-Nb2O5-180/CuO-1%) had the best response, with a TON value of 370, which corresponds to a 5-fold increase in relation to the reference sample formed by the sensitization of exfoliated hexaniobate (Re-K4-xHxNb6O17esf). The sensitized composite exhibited also greater stability for long periods of irradiation. Mechanistic studies indicate that CuO acts as a sensitizer and plays a fundamental role in the photocatalytic activity. Nb2O5, on the other hand, acts as an electron storage, improving charge separation and increasing the lifetime of photogenerated charges. The Re(I) complex acts as a catalytic center after being photoactivated and guarantees the selectivity of the system. The results are a considerable advance towards the development of more efficient hybrid photocatalysts for CO2 reduction.